Analysis of “Ideas” in Mohd. Affandi Hassan’s Espens - Arukin, Nahari Mastono (2008)
This study stems from early observations which have uncovered two different viewpoints on the aspect of “ideas” in contemporary Malay literature. On the one hand, Malay literary works are said to offer certain “ideas” that are clear and serious. On the other hand, the presence of “ideas” in Malay literary writings is also questioned and contested. These two contradicting viewpoints have motivated this study to further analyse the aspect of “ideas” in Malay literature. Thus, this study analyses the works of Mohd. Affandi Hassan, a creative writer and renowned critic of Malay literature. This choice is based on Mohd. Affandi’s reputation as a well known contemporary writer who relentlessly calls for an emphasis on the aspect of “ideas” in literary texts. This also raises the question of whether Mohd. Affandi could realise his own call. To answer this question, the study scrutinises 20 of Mohd. Affandi’s espens for the purpose of analysis. The espen genre is chosen because Mohd. Affandi conceptualises this genre (espen) to convey “ideas”. Therefore, this study incorporates the ideas of “Persuratan Baru” (PB or Genuine Literature), mooted by Mohd. Affandi, as a framework for analysis. Among the ideas of PB incorporated are differentiating between “ilmu” or “knowledge” (“ideas”) and “cerita” (“story”) which is a basic aspect of espen. This study has several findings. Among them, “ideas” exist in the studied texts and are conveyed through academic writing. This tendency also places the “story” in a subordinate position.